Testing for fecal gluten immunogenic peptides: a useful tool to evaluate compliance with gluten-free diet by celiacs - Porcelli, Brunetta (Ann Gastroenterol, 2020)
BACKGROUND: Although experts agree that strict dietary compliance is fundamental for the health of celiac patients, there are no evidence-based recommendations on the best way to assess dietary compliance. Detection of gluten immunogenic peptides (GIPs) in feces was recently proposed as an effective method of assessing the dietary compliance of celiac patients. METHODS: Fifty-five consecutive celiac patients (27 adults and 28 children, age 6-72 years), who had been on a gluten-free diet for at least 2 years, were enrolled. All patients were evaluated clinically for symptoms, physical parameters and laboratory parameters. Dietary compliance was assessed with the Biagi questionnaire and serum anti-tissue transglutaminase (tTG) IgA antibodies were measured. GIPs were determined by immunoenzymatic assay on an automated Chorus analyzer (DIESSE Diagnostica Senese), after extraction of fecal samples by the method developed by DIESSE. RESULTS: Eight patients tested positive for GIPs (GIPs+); 71.4% of GIP-positive patients were asymptomatic; tTG antibodies were detected in 3/8 GIP+ patients. The Biagi score was significantly associated with fecal positivity for GIPs (P=0.02). However, according to the Biagi score, 57.1% of GIP+ patients followed the diet strictly and 5.4% of GIP- subjects did not comply with the diet or made substantial mistakes. CONCLUSIONS: Assay of fecal GIPs identified more patients who did not comply with the diet than did the Biagi questionnaire, evaluation of symptoms or anti-tTG antibodies. Detection of fecal GIPs offers a direct, objective, quantitative assessment of even occasional exposure to gluten and is confirmed as a practical way to check dietary compliance.